Alterations of presynaptic proteins in autism spectrum disorder - Yeo, Xin Yi; Lim, Yi Tang; Chae, Woo Ri; Park, Chungwon; Park, Hyokeun; Jung, Sangyong (Frontiers in Molecular Neuroscience, 2022)
The expanded use of hypothesis-free gene analysis methods in autism research has significantly increased the number of genetic risk factors associated with the pathogenesis of autism. A further examination of the implicated genes directly revealed the involvement in processes pertinent to neuronal differentiation, development, and function, with a predominant contribution from the regulators of synaptic function. Despite the importance of presynaptic function in synaptic transmission, the regulation of neuronal network activity, and the final behavioral output, there is a relative lack of understanding of the presynaptic contribution to the pathology of autism. Here, we will review the close association among autism-related mutations, autism spectrum disorders (ASD) phenotypes, and the altered presynaptic protein functions through a systematic examination of the presynaptic risk genes relating to the critical stages of synaptogenesis and neurotransmission.